Characterization and investigation of biological properties of silver nanoparticle-doped hydroxyapatite-based surfaces on zirconium - Yildiz, Tuba; Durdu, Salih; Ozcan, Kadriye; Usta, Metin (Nature Portfolio, 2023)
The infections leading to failed implants can be controlled mainly by metal and metal oxide-based nanoparticles. In this work, the randomly distributed AgNPs-doped onto hydroxyapatite-based surfaces were produced on zirconium by micro arc oxidation (MAO) and electrochemical deposition processes. The surfaces were characterized by XRD, SEM, EDX mapping and EDX area and contact angle goniometer. AgNPs-doped MAO surfaces, which is beneficial for bone tissue growth exhibited hydrophilic behaviors. The bioactivity of the AgNPs-doped MAO surfaces is improved compared to bare Zr substrate under SBF conditions. Importantly, the AgNPs-doped MAO surfaces exhibited antimicrobial activity for E. coli and S. aureus compared to control samples.
Keywords: In-Vitro Properties; Micro-Arc Oxidation; Bioceramic Coatings; Bioactive Coatings; Composite Coatings; Antibacterial; Fabrication; Alloy; Ag; Ha